The Activity of Chemotherapy in Inflammatory Myofibroblastic Tumors: A Multicenter, European Retrospective Case Series Analysis. (12th July 2020) - Baldi, Giacomo Giulio; Brahmi, Mehdi; Lo Vullo, Salvatore; Cojocaru, Elena; Mir, Olivier; Casanova, Michela; Vincenzi, Bruno; De Pas, Tommaso Martino; Grignani, Giovanni; Pantaleo, Maria Abbondanza; Blay, Jean Yves; Jones, Robin Lewis; et al.
Abstract: Background: This study aimed to review the activity of cytotoxic chemotherapy in patients with inflammatory myofibroblastic tumors (IMTs) treated at nine European sarcoma reference centers. Materials and Methods: Patients of any age, with histologically proven IMT, treated with anthracycline‐based methotrexate plus/minus vinorelbine/vinblastine (MTX‐V) or other chemotherapeutic regimens between 1996 and 2018 were retrospectively reviewed. Diagnosis was confirmed at the local level by an expert pathologist. Response was retrospectively assessed by local investigators by RECIST v1.1. Progression‐free survival (PFS), relapse‐free survival (RFS), and overall survival (OS) were computed by Kaplan‐Meier method. Results: Thirty‐eight patients were included. Twenty‐five patients (8 localized, 17 advanced disease) received an anthracycline‐based regimen; 21 were evaluable for response. Overall response rate (ORR) was 10/21 (47.6%). At a 70.8‐month median follow‐up (FU), median RFS and median OS were not reached (NR) in patients with localized disease; median PFS and median OS were 6.3 (interquartile range [IQR]: 1.9–13.4) and 21.2 (IQR: 7.7–40.7) months in patients with advanced disease. Thirteen patients received MTX‐V (4 localized, 9 advanced disease), all evaluable for response. ORR was 7/13 (53.8%). At a 56.6‐month median FU, median RFS and median OS were 42.5 (IQR: 12.9–61.2) months and NR (no death events) in patients with localized disease, and NR (IQR: 24.9 to NR) and 83.4 months (IQR: 83.4 to NR) in patients with advanced disease. In the "other‐regimens group, " responses were seen in 3/4 patients treated with oral cyclophosphamide and 1/2 with docetaxel/gemcitabine. Conclusion: Anthracycline‐based and MTX‐V regimens are very effective in IMT, with a similar ORR in both groups. MTX‐V achieved a prolonged disease control. Responses were also seen with oral cyclophosphamide and docetaxel/gemcitabine, but few patients were treated with these schedules. Implications for Practice: Inflammatory myofibroblastic tumor (IMT) is an ultrarare sarcoma with known sensitivity to anaplastic lymphoma kinase (ALK) inhibitors in ALK‐fused cases, although ALK inhibitors are not licensed in the disease. The current knowledge on the activity of cytotoxic chemotherapy is limited. This multi‐institutional retrospective study on pediatric and adult patients with IMT shows that cytotoxic chemotherapy, and in particular anthracycline‐based and methotrexate plus/minus vinorelbine/vinblastine regimens, represents a treatment option and can be considered in IMT patients irrespectively from ALK status. This study provides a benchmark for future studies on new medical therapies. Abstract : This article reports on the activity of cytotoxic chemotherapy in patients with inflammatory myofibroblastic tumors, focusing on anthracycline‐based regimens, the front‐line standard treatment in sarcomas, and methotrexate and/or vinorelbine or vinblastine. Data available on other cytotoxic regimens are also reported.